Differentiated HIV care in South Africa: the effect of fast‐track treatment initiation counselling on ART initiation and viral suppression as partial results of an impact evaluation on the impact of a package of services to improve HIV treatment adherence. Issue 11 (5th November 2019) - Pascoe, Sophie JS; Fox, Matthew P; Huber, Amy N; Murphy, Joshua; Phokojoe, Mokgadi; Gorgens, Marelize; Rosen, Sydney; Wilson, David; Pillay, Yogan; Fraser‐Hurt, Nicole
Abstract: Introduction: In response to suboptimal adherence and retention, South Africa's National Department of Health developed and implemented National Adherence Guidelines for Chronic Diseases. We evaluated the effect of a package of adherence interventions beginning in January 2016 and report on the impact of Fast‐Track Treatment Initiation Counselling (FTIC) on ART initiation, adherence and retention. Methods: We conducted a cluster‐randomized mixed‐methods evaluation in 4 provinces at 12 intervention sites which implemented FTIC and 12 control facilities providing standard of care. Follow‐up was by passive surveillance using clinical records. We included data on subjects eligible for FTIC between 08 Jan 2016 and 07 December 2016. We adjusted for pre‐intervention differences using difference‐in‐differences (DiD) analyses controlling for site‐level clustering. Results: We enrolled 362 intervention and 368 control arm patients. Thirty‐day ART initiation was 83% in the intervention and 82% in the control arm (RD 0.5%; 95% CI: −5.0% to 6.0%). After adjusting for baseline ART initiation differences and covariates using DiD we found a 6% increase in ART initiation associated with FTIC (RD 6.3%; 95% CI: −0.6% to 13.3%). We found a small decrease in viral suppression within 18 months (RD −2.8%; 95% CI: −9.8% to 4.2%) with no difference after adjustment (RD: −1.9%; 95% CI: −9.1% to 5.4%) or when considering only those with a viral load recorded (84% intervention vs. 86% control). We found reduced crude 6‐month retention in intervention sites (RD −7.2%; 95% CI: −14.0% to −0.4%). However, differences attenuated by 12 months (RD: −3.6%; 95% CI: −11.1% to 3.9%). Qualitative data showed FTIC counselling was perceived as beneficial by patients and providers. Conclusions: We saw a short‐term ART‐initiation benefit to FTIC (particularly in districts where initiation prior to intervention was lower), with no reductions but also no improvement in longer‐term retention and viral suppression. This may be due to lack of fidelity to implementation and delivery of those components that support retention and adherence. FTIC must continue to be implemented alongside other interventions to achieve the 90‐90‐90 cascade and fidelity to post‐initiation counselling sessions must be monitored to determine impact on longer‐term outcomes. Understanding the cost‐benefit and role of FTIC may then be warranted.